Measurement Of The Level Of Competitiveness And Determinants Of Southeast Sulawesi Cocoa Trade - Masitah, Masitah; Bahari, Doddy Ismunandar; Amaliah, Annisa; Prihantini, Campina Illa; Nursalam; Wulandary, Ayu; Khaerunnisa, Khaerunnisa (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
The objective of this research is to see the development of cocoa competitiveness and its determining factors in the Southeast Sulawesi trade. The data used in the study were collected from several institutions, namely Central Statistics Agency, the Ministry of Agriculture, and the International Cocoa Organization (ICCO), in the form of time series data from 2011-2022. The research methodology applied the Revealed Comparative Advantage (RCA) for determining the development of cocoa competitiveness and Multiple Linear Regression Analysis for the determinants of cocoa trade. The results of the analysis show that Southeast Sulawesi's superior cocoa commodity has competitiveness. The RCA value can be seen from 2011 to 2018 and is still quite good. It is proven that the average RCA is above 4, although in the following year the RCA value shows a decreasing trend until 2022. Moreover, the determining factors for the competitiveness of Southeast Sulawesi’s cocoa are land area, production factors, domestic prices and international prices. Only the domestic price variable partially has a notable effect on its competitiveness. This research can be made a reference for the local government to adopt any policies regarding the export of cocoa beans and processed products so that it can encourage and increase the competitiveness of Southeast Sulawesi cocoa through implementing downstreaming, improving infrastructure and national cocoa research and development.